Commercial Aviation Safety - Lawrenson, Anthony; Rodrigues, Clarence C.; Malmquist, Shem; Greaves, Matthew; Braithwaite, Graham; Cusick, Stephen K. (McGraw Hill, 2023)
This thoroughly revised guide covers all the principles and practices of commercial aviation safety-from human factors and accident investigation to management strategies and regulatory compliance. Written by a team of experts, Commercial Aviation Safety, Seventh Edition delivers comprehensive risk management information-both on the ground and in the air. You will get plain-language explanations of the latest standards from the National Transportation Safety Board (NTSB), Federal Aviation Administration (FAA), and International Civil Aviation Organization (ICAO). Up-to-date U.S. and international accident statistics also are included. Each section of the book begins with a detailed real-world example before diving into analyses and explanations of core issues